2016
DOI: 10.1093/cid/ciw364
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Toxin B Are Protective AgainstClostridium difficileInfection Recurrence

Abstract: NCT00350298.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 25 publications
5
44
1
1
Order By: Relevance
“…An analysis of samples from this study by Gupta et al found that naturally occurring anti-TcdB, but not antiTcdA (as measured by ELISA) within placebo recipients offered protection against recurring CDI [30]. These findings stand in contrast to the aforementioned study that found patients with an initial episode of CDI were protected against recurrence by antiTcdA antibodies [19].…”
Section: Anti-c Difficile Antibodies In Primary Versus Recurring CDIcontrasting
confidence: 70%
See 2 more Smart Citations
“…An analysis of samples from this study by Gupta et al found that naturally occurring anti-TcdB, but not antiTcdA (as measured by ELISA) within placebo recipients offered protection against recurring CDI [30]. These findings stand in contrast to the aforementioned study that found patients with an initial episode of CDI were protected against recurrence by antiTcdA antibodies [19].…”
Section: Anti-c Difficile Antibodies In Primary Versus Recurring CDIcontrasting
confidence: 70%
“…administration, the nanoparticle vaccine offered full protection from C. difficile, and provided long lasting Ab titers against antigen, compared to aluminum adjuvanted rTcdB [45]. Hong and colleagues developed a Bacillus subtilis spore-based oral vaccine consisting of a specific region of TcdA CBD (TcdA [26][27][28][29][30][31][32][33][34][35][36][37][38][39] ) and tested its efficacy in a hamster model. Hamsters immunized with the oral vaccine and challenged with C. difficile developed anti-TcdA CBD mucosal Abs that prevented colonization of C. difficile.…”
Section: Active Immunization Against C Difficilementioning
confidence: 99%
See 1 more Smart Citation
“…Most recently a randomized, double-blind, placebo-controlled study of two neutralizing, fully human monoclonal antibodies against C. difficile toxins A (CDA1) and B (CDB1) in patients with symptomatic C. difficile diarrhea demonstrated decrease recurrence of C. difficile infection [29]. Toxin B is essential for disease while Toxin A may not be [30], a recent multivariate analysis of the placebo arm of the aforementioned trial found that in this study the main predictor for C. difficile infection recurrence was age >65 (OR 3.93, p 0.09), meanwhile, antibodies to toxin B were found to be protective against disease recurrence (OR 0.11, p 0.05) [31]. …”
Section: Lymphocytesmentioning
confidence: 78%
“…Now, in this issue of Clinical Infectious Diseases, Gupta and colleagues provide more interesting data from that study [7]. They report on predictors of recurrence in the 99 placebo-treated patients.…”
mentioning
confidence: 99%